Design of a 3DoF Passive Hip Exoskeleton for Rehabilitation - Arrieta Conde, Joaquin (2024)
In recent years, many mechanisms have been developed to help people with reduced mobility, especially for people with injuries that impede the mobility of the lower part with respect to the hip. That is why this work presents the design of a passive hip-based exoskeleton of a standard size so that it can be used in the rehabilitation area. Most hip exoskeletons make a strong call on walking assistance rather than on the stability of the user, so the design is adjusted to the stability, the objective of this work is to design a self-balancing exoskeleton with control by sensors that detect the hip rotation and send a signal to the microcontroller which assists the movement of the hip, allowing the servos to move according to the degrees detected by the sensor. In addition, the exoskeleton has been designed using CAE software, using aluminum elements to provide lightness and robustness to the exoskeleton and, at the same time, an external PLA plastic shell is made, in order to provide lightness, flexibility and limited volume, when performing a stress test shows optimal results that allows us to know the durability and comfort of the exoskeleton.